Agrarian change, cattle ranching and deforestation: Assessing their linkages in Southern Para - Pacheco, P. (2009)
In this paper, I illustrate the dynamics of frontier development in the Redencao area in southern Para, one of the oldest agricultural frontiers in the Brazilian Amazon. This frontier has evolved from a landscape initially dominated by large-scale corporations investing in cattle ranching, to another in which medium-scale cattle ranchers and to less extent smallholders expanded their influence in the local economy. The initial stage was driven by fiscal incentives and subsidies from the government. The latter stage features more developed markets for beef and milk products, and is associated with an expansion of slaughterhouses and dairy processing plants, the modernisation of livestock production, fragmentation of large estates, and competition for land. The latter phase originated with the arrival of new investors in medium-scale cattle ranching, and with expanding pressure from smallholders and landless people looking for land. The process of land occupation and agrarian development has inevitably led to forest conversion mainly to pasture. Finally, environmental policies seeking to halt deforestation have been largely ineffective under these conditions of frontier development.